Efektivitas Peran dan Fungsi Kepala Ruangan dalam Menurunkan Angka Kejadian Insiden Keselamatan Pasien Rawat Inap - Susanti, Yeni; Tarigan, Emiliana (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2025)
The role and function of the head nurse in nursing services is crucial, as they hold full responsibility for ensuring safe and high-quality nursing care practices. However, several issues related to the role and function of head nurses are still found, such as a lack of control in preventing incidents, limited knowledge of patient safety, and suboptimal development of their competencies. This study aims to analyze the role and function of head nurses in reducing the number of inpatient patient safety incidents in hospitals.The research employed a literature review method by analyzing articles from databases such as Scopus, ScienceDirect, ProQuest, and Google Scholar in 2020 - 2024. The results show that the role and function of head nurses are more effective in reducing patient safety incidents. This effectiveness is influenced by several factors, including: (1) limited knowledge and skills of head nurses regarding patient safety; (2) the absence of clear standard operating procedures (SOPs) outlining their roles and functions; (3) lack of managerial support from hospital leadership; and (4) low awareness and commitment among nurses in implementing patient safety measures. Efforts to improve the effectiveness of the head nurse’s role and function can be achieved through targeted training to enhance their competencies and the development of clear SOPs related to their responsibilities.